Plan de capacitación para reducir la violencia intrafamiliar en la parroquia de Olmedo en el período Enero-Septiembre 2024. - Guamaní Obando, Nayelly Estefanía (2024)
The present research has as its study setting the physical violence against women that has been present since the first moments of society, manifestingit self inside and outsidethe home, which has caused permanent damage and death in the victims. The Constitution of the Republic of Ecuador guarantees the physical integrity of the membersof the family core. The aggressions that occur in the family environment can affect the physical, psychological and emotional development of its members, therefore the Ecuadorian legal system provides them protection. In a constitutional state of rights andjustice like ours, the state not only has the obligation to respect and guarantee equality and non discrimination, either by eliminating norms or practices that perpetuate its violation, or by adopting norms or practices that make this principle effective without discrimination de jure or de facto, including the adoption of positive measures to reverseor change these discriminatory situations; but also has the obligation to guarantee women's right to a life free of violence, which includes their responsibility to take the necessary measures so that women in situations of domestic violence have effective access to suitable resources. Human rights are analyzed from a critical perspective provided by feminist legal theorists. The problem of violence against women is analyzed as one of the most systematic forms of human rights violations.